2017
DOI: 10.4103/ijpvm.ijpvm_322_16
|View full text |Cite
|
Sign up to set email alerts
|

Effect of angiotensin-converting enzyme inhibitor on cardiac fibrosis and oxidative stress status in lipopolysaccharide-induced inflammation model in rats

Abstract: Background:Renin-angiotensin (Ang)-aldosterone system not only plays a key role in the regulation of circulatory homeostasis, but also it acts as a powerful pro-inflammatory mediator. The aim of this study was to evaluate the effect of captopril (Cap), a known Ang-converting enzyme inhibitor, on inflammation-induced cardiac fibrosis, and heart oxidative stress status in lipopolysaccharide (LPS)-induced inflammation in male rats.Methods:Fifty male rats were randomly divided into five groups control, LPS (1 mg/k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…The inhibition of ACE reduces angiotensin II which will cause fibrotic effects through the AT1 receptor, and also enhance the reduction effect by increasing bradykinin; this would be the advantage of ACEIs over AT-1 receptor blockers on reducing cardiac fibrosis. A study from Abareshi et al (74) showed that ACEIs reduce inflammation and fibrosis through the reduction of IL-6 and TNF-α. Deijanera et al (75) demonstrated the ACEIs have an effect on reducing TGF-β1, TGF-β2, and Th2 cytokines.…”
Section: The Role Of Aceis In Cardiac Fibrosis In Rhdmentioning
confidence: 99%
“…The inhibition of ACE reduces angiotensin II which will cause fibrotic effects through the AT1 receptor, and also enhance the reduction effect by increasing bradykinin; this would be the advantage of ACEIs over AT-1 receptor blockers on reducing cardiac fibrosis. A study from Abareshi et al (74) showed that ACEIs reduce inflammation and fibrosis through the reduction of IL-6 and TNF-α. Deijanera et al (75) demonstrated the ACEIs have an effect on reducing TGF-β1, TGF-β2, and Th2 cytokines.…”
Section: The Role Of Aceis In Cardiac Fibrosis In Rhdmentioning
confidence: 99%
“…13 We also previously showed that ACE inhibitors including captopril had some anti-oxidant effects. 30,31 Thus, the ability of captopril to reverse PTZ-induced seizures which was observed in the current study may at least in part be due to enhancement of antioxidant defense system and attenuation of oxidative stress in the brain. 32 This action might be resulted from its ability to overcome the pro-oxidant effects of PTZ-induced seizures, through increase in antioxidant defense systems including GSH, SOD and CAT and a decrease in MDA and nitrite levels in the brain.…”
Section: Discussionmentioning
confidence: 63%
“…CAP, an angiotensin-converting enzyme inhibitor commonly used in clinic, has been reported that is effective at ameliorating MF ( Abareshi et al, 2017 ; Wang et al, 2019c ), so it was used as a positive control in this study. According to our present results, 8-Gin produced an anti-fibrotic effect similar to that of CAP, but the therapeutic effect of CAP was stronger than 8-Gin.…”
Section: Discussionmentioning
confidence: 99%